Validity and Reliability Testing of the Gratitude Scale Among University Students Using the Partial Least Squares Structural Equation Modeling (PLS-SEM) Approach - Arthadi Fitria Utami; Herdian Herdian; Retno Dwiyanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Gratitude is a fundamental affective disposition that plays a crucial role in enhancing university students' psychological well-being and resilience amid academic pressures. However, a methodological gap remains in the use of gratitude measurement instruments within the Indonesian context, as many studies continue to rely on adapted Western scales without rigorous cross-validation and depend primarily on traditional reliability testing. This study aimed to examine the validity and reliability of a Gratitude Scale adapted based on the dimensions of intensity, frequency, span, and density using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The participants consisted of 151 active university students in Indonesia selected through convenience sampling. Sample adequacy was verified using the inverse square root method. The results indicated that, after removing items with negative outer loadings, the instrument demonstrated satisfactory convergent validity, with an Average Variance Extracted (AVE) exceeding 0.50 and Composite Reliability values above 0.70 across all dimensions. However, discriminant validity assessment using the Heterotrait–Monotrait Ratio (HTMT) criterion revealed that several dimensions exhibited very high correlations (HTMT > 0.90), suggesting that the gratitude construct within this population is holistic in nature and difficult to distinguish empirically across its dimensions. These findings confirm the overall psychometric robustness of the scale while highlighting the need for further theoretical consideration regarding the multidimensional structure of gratitude in collectivist cultural contexts.